Pengaruh Content Marketing Dan Event Marketing Terhadap Brand Image Honda Pada Masyarakat Kelurahan Mangga, Medan - Siburian, Ester; Hasman, Haryaji Catur Putera (Universitas Medan Area, 2024)
This research aims to determine the influence of Content Marketing and Event Marketing on the Brand Image of Honda Motorcycles in the Community of Mangga Village, Medan. This type of research is quantitative associative research. The population in this study is the people of Mangga sub-district, Medan who own Honda motorbikes, with a sample size of 100 respondents. The data collection technique in this research uses a questionnaire with a quantitative approach. The data analysis techniques used are descriptive statistical analysis and multiple regression analysis. Then test the hypothesis using the Partial Test (t Test) and Simultaneous Test (f Test). The research results show that partially Content Marketing has a positive and significant effect on Brand Image and Event Marketing has a positive and significant effect on Brand Image. Simultaneously Content Marketing and Event Marketing have a positive and significant effect on Brand Image